Intracellular CHO Cell Metabolite Profiling Reveals Steady‐State Dependent Metabolic Fingerprints in Perfusion Culture. (3rd March 2017) - Karst, Daniel J.; Steinhoff, Robert F.; Kopp, Marie R. G.; Serra, Elisa; Soos, Miroslav; Zenobi, Renato; Morbidelli, Massimo
Abstract : Perfusion cell culture processes allow the steady‐state culture of mammalian cells at high viable cell density, which is beneficial for overall product yields and homogeneity of product quality in the manufacturing of therapeutic proteins. In this study, the extent of metabolic steady state and the change of the metabolite profile between different steady states of an industrial Chinese hamster ovary (CHO) cell line producing a monoclonal antibody (mAb) was investigated in stirred tank perfusion bioreactors. Matrix‐assisted laser desorption/ionization time of flight mass spectrometry (MALDI‐TOF‐MS) of daily cell extracts revealed more than a hundred peaks, among which 76 metabolites were identified by tandem MS (MS/MS) and high resolution Fourier transform ion cyclotron resonance (FT‐ICR) MS. Nucleotide ratios (Uridine (U)‐ratio, nucleotide triphosphate (NTP)‐ratio and energy charge (EC)) and multivariate analysis of all features indicated a consistent metabolite profile for a stable culture performed at 40 × 10 6 cells/mL over 26 days of culture. Conversely, the reactor was operated continuously so as to reach three distinct steady states one after the other at 20, 60, and 40 × 10 6 cells/mL. In each case, a stable metabolite profile was achieved after an initial transient phase of approximately three days at constant cell density when varying between these set points. Clear clustering according to cell density was observed by principal component analysis, indicating steady‐state dependent metabolite profiles. In particular, varying levels of nucleotides, nucleotide sugar, and lipid precursors explained most of the variance between the different cell density set points. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 33:879–890, 2017